Evaluación del funcionamiento de una familia con un adolescente con Trastorno Afectivo Bipolar - Restrepo Rivera, Angélica María (2022)
This article describes a systemic assessment of a family with an adolescent member diagnosed with bipolar affective disorder. The data on family processes was analyzed using four categories: boundaries, communication patterns, individual and family life cycle and family beliefs. Main results showed disturbances in the four assessed areas. Rigid boundaries, low cohesion within members, high conflict levels inside and between subsystems, high expressed emotions, unaccomplished developmental tasks and beliefs related to family life that prevented a more adequate management of the illness. Systemic family assessment is highlighted as a useful tool to plan and conduct family therapy.